1991
DOI: 10.1159/000247755
|View full text |Cite
|
Sign up to set email alerts
|

Topical Retinoic Acid Does Not Alter the Vasoconstrictive Properties of Topical Corticosteroids in Humans

Abstract: Dermo-epidermal atrophy is one of the main side effects of long-term treatment with topical corticosteroids. Retinoic acid may prevent and even reverse these effects in animals. Extension of this concept to therapy in humans implies that several studies have been performed; among others, it has to be established that treatment with topical retinoic acid does not interfere with the anti-inflammatory action of topical corticosteroids. The present study on the cutaneous vasoconstriction test comprised two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This is concordant with our pre vious observation [8] that this association has the same vasoconstrictive activity as the steroid alone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is concordant with our pre vious observation [8] that this association has the same vasoconstrictive activity as the steroid alone.…”
Section: Discussionsupporting
confidence: 92%
“…That RA may be used to prevent topical steroid-induced atrophy in human requires different steps of analysis. We have previously shown [8] that pretreatment of normal skin with topical RA 0.05, 0.025 and 0.01% did not inhibit corticosteroid-induced vasoconstriction; this suggested that RA may not interfere with the anti-inflammatory property of the ste roid. It was also found that the vasoconstrictive activity of triamcinolone acetonide (TA) 0.1% was preserved when 0.025% RA was added in the same preparation, indicating that the mixture may have anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 95%
“…Repeated daily application during 4 consecutive d of the different compounds did not induce noticeable erythema, scaling or infiltration at the site of application except for the typical halo of vasoconstriction when corticosteroids were applied, both pure or in association with retinoie acid, as previously 1-eported (13).…”
Section: Resultsmentioning
confidence: 72%
“…These have been explored for therapeutic use as well as to countetact the side effects of each other (11)(12)(13)(14); little data is currently available on the tnolecuiar mechanism of this interaction in human skin in vivo. These have been explored for therapeutic use as well as to countetact the side effects of each other (11)(12)(13)(14); little data is currently available on the tnolecuiar mechanism of this interaction in human skin in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation